(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
The advent of digital technologies has fundamentally reshaped various sectors, and education is no exception. This article explores the growing significance of educational innovations powered by digital technologies, particularly in the context of personalized learning, accessibility, and the future of work. The integration of Artificial Intelligence (AI), Virtual Reality (VR), Augmented Reality (AR), and online learning platforms are revolutionizing how education is delivered, consumed, and assessed. The article also discusses the implications of these advancements in fostering lifelong learning, providing equal opportunities, and preparing students for an increasingly digital economy. As education becomes more flexible and learner-centered, it offers greater potential for global knowledge sharing and transformation.